Enhancing Personnel Management: A Study on the Implementation of SIMPEG in the Batam City Staffing and Human Resources Development Agency - Hafizhah Nurul Katresna; Etika Khairina; Lubna Salsabila (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
This study examines Batam City's adoption of the Personnel Management Information System (SIMPEG) to digitize employee data for personnel management reform. SIMPEG integrates employee data, data management, work processes, human resources, and information technology for effective and accurate personnel administration. The Batam City Regional Personnel Agency's personnel data digitization is the focus of the research, which seeks to discover SIMPEG system support and barriers. This study uses qualitative analysis to explain how personnel data digitization helps create the SIMPEG application in Batam City. The study examines SIMPEG system elements such state civil servant master data, mapping, statistical analysis, predictive modeling, reporting, and user management. The research examines these elements to evaluate the SIMPEG system's impact on Batam City's personnel management. This research also examines the Batam City Regional Personnel Agency's methods for digitizing personnel data and optimizing SIMPEG use. This study illuminates how digitizing personnel data improves staff management in Batam City. Supporting variables can be used as best practices for other regions and organizations adopting similar systems, while inhibiting factors can assist guide future implementation tactics and prevent mistakes. This research seeks to improve public administration information system usage knowledge. This study aims to improve Batam City's governance by highlighting SIMPEG's successes and challenges